Carbon quantum dots reinforced hydrogel, and preparation method and application thereof

CN122772235APending Publication Date: 2026-09-18SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610918915.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

然而,常规聚合物凝胶在高温(>90℃)、高矿化度(>20×104mg/L)的气藏环境中面临严峻挑战:高温环境加速聚合物分子链的热氧降解,高矿化度环境压缩聚合物水化层导致分子链收缩甚至析出,造成凝胶网络逐渐疏松、脱水收缩,封堵强度大幅衰减

Benefits of technology

本发明能够制得具优异的注入性、高封堵强度、长效稳定性及气水选择性封堵能力的碳量子点强化水凝胶,用其可有效抑制气藏边底水窜流,显著提高气藏采收率,适用于高温高盐气藏深部控水工程,具有广阔的现场应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122772235A_ABST
    Figure CN122772235A_ABST
Patent Text Reader

Abstract

The application discloses carbon quantum dot reinforced hydrogel and a preparation method and application thereof, and the preparation method comprises the following steps: S1, carbon quantum dots containing amino groups, carboxyl groups, phenolic hydroxyl groups and aromatic rings are prepared by using a carbon source, a nitrogen source and a modifier; the modifier is a mixture of hydroquinone and L-alanine; S2, the carbon quantum dots are subjected to hydroxymethylation by using hexamethylenetetramine to obtain hydroxymethylated carbon quantum dots; and S3, the hydroxymethylated carbon quantum dots are used as a crosslinking agent, and the hydroxymethylated carbon quantum dots are mixed with a polymer main agent, a stabilizer and a solvent to obtain the carbon quantum dot reinforced hydrogel through crosslinking reaction. The carbon quantum dot reinforced hydrogel with excellent injectivity, high plugging strength, long-term stability and gas-water selective plugging capacity can be prepared, gas reservoir edge and bottom water channeling can be effectively inhibited by using the carbon quantum dot reinforced hydrogel, gas reservoir recovery can be significantly improved, the carbon quantum dot reinforced hydrogel is suitable for high-temperature and high-salt gas reservoir deep water control engineering, and has a wide field application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oil and gas field development engineering technology, and in particular to a carbon quantum dot reinforced hydrogel, its preparation method and application. Background Technology

[0002] During the development of edge-water gas reservoirs, as formation pressure gradually decreases, edge-water, under the influence of pressure differential, flows towards the gas well along advantageous channels such as high-permeability strips and fractures. This leads to premature water breakthrough, reduced production capacity, and even water flooding shutdown, severely restricting the improvement of gas reservoir recovery. Chemical water control technology, which injects water-blocking agents into the formation to regulate the two-phase flow of gas and water from within the reservoir, is considered a technology with long-term remediation potential.

[0003] Polymer hydrogels have become an important development direction in chemical water control materials due to their ability to construct three-dimensional network structures, high plugging strength, and ease of functional modification. However, conventional polymer gels have limitations in high-temperature (>90℃) and high-mineralization (>20×10⁻⁶) conditions. 4 In gas reservoirs with concentrations of mg / L, the well faces severe challenges: high temperatures accelerate the thermo-oxidative degradation of polymer molecular chains, and high salinity environments compress the polymer hydration layer, causing molecular chain shrinkage or even precipitation. This results in a gradual loosening and dehydration of the gel network, leading to a significant decrease in plugging strength. Furthermore, conventional gels lack selectivity for both gas and aqueous phases, making them prone to "water and gas blockage," thus reducing gas well productivity. Summary of the Invention

[0004] The purpose of this invention is to provide a carbon quantum dot reinforced hydrogel, its preparation method, and its application.

[0005] The technical solution of the present invention is as follows: On the one hand, a method for preparing carbon quantum dot-reinforced hydrogels is provided, comprising the following steps: S1: Carbon quantum dots with amino, carboxyl, phenolic hydroxyl groups and aromatic rings on their surface are prepared using a carbon source, a nitrogen source and a modifier; the modifier is a mixture of hydroquinone and L-alanine; S2: The carbon quantum dots are hydroxymethylated with hexamethylenetetramine to obtain hydroxymethylated carbon quantum dots; S3: Using the hydroxymethylated carbon quantum dots as a crosslinking agent, mix them with a polymer agent, a stabilizer, and a solvent to obtain the carbon quantum dot-reinforced hydrogel through a crosslinking reaction; the polymer agent can crosslink with the hydroxymethylated carbon quantum dots to form a dense and stable three-dimensional network.

[0006] Preferably, in step S1, the carbon source is any one or more of sodium citrate, citric acid, and glucose, and the nitrogen source is any one or more of urea, ethylenediamine, and o-phenylenediamine.

[0007] Preferably, in step S1, the molar ratio of the carbon source, nitrogen source, hydroquinone, and L-alanine is 5~8:3:2~5:1.

[0008] Preferably, in step S1, the carbon quantum dots are prepared by solid-state pyrolysis, with a pyrolysis temperature of 170~210℃ and a pyrolysis time of 0.8~1.2h.

[0009] Preferably, in step S2, the hydroxymethylation is carried out at 60-80°C and pH=7.0-8.0 for 2-3 hours.

[0010] Preferably, in step S3, the mixing includes 0.4-0.8 wt% of a crosslinking agent, 0.6-1.0 wt% of a polymer main agent, 0.03-0.07 wt% of a stabilizer, and the balance being the solvent.

[0011] Preferably, in step S3, the crosslinking reaction is carried out at 90~150℃ for 6~12h.

[0012] Preferably, in step S3, the polymer main agent is a temperature- and salt-resistant polyacrylamide, the stabilizer is any one or more of thiourea, sodium sulfite, sodium dithionite, and sodium isoascorbate, and the solvent is water.

[0013] On the other hand, a carbon quantum dot reinforced hydrogel prepared by any one of the above methods and its application in gas reservoir water control are also provided.

[0014] The beneficial effects of this invention are: This invention can produce carbon quantum dot-reinforced hydrogels with excellent injectability, high plugging strength, long-term stability, and selective gas-water plugging capability. These hydrogels can effectively suppress water channeling at the edge and bottom of gas reservoirs, significantly improve gas recovery, and are suitable for deep water control projects in high-temperature and high-salinity gas reservoirs, with broad prospects for field applications. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a transmission electron microscope image of carbon quantum dots from Example 1; Figure 2 This is a particle size distribution chart of carbon quantum dots from Example 1; Figure 3The images show AFM morphology micrographs and 3D side morphology micrographs of carbon quantum dots in Example 1; where (a) is an atypical local region of the sample; and (b) is a typical local region of the sample. Figure 4 This is a height profile of the carbon quantum dots in Example 1; where (a) is an atypical local region of the sample; and (b) is a typical local region of the sample. Figure 5 The Fourier transform infrared spectrum of the carbon quantum dots in Example 1; Figure 6 Thermogravimetric analysis curve of carbon quantum dots in Example 1; Figure 7 Comparison of the states of polymer gels with different types of crosslinking agents after 30 days of aging; Figure 8 Pressure change curves were injected into different systems; where (a) is the test result of Example 1; and (b) is the test result of Comparative Example 1. Figure 9 The curves showing the changes in injection pressure of the hydrogel in Example 1 are shown; where (a) is the test result using mineralized water as the core test fluid; and (b) is the test result using CH4 as the core test fluid. Figure 10 The curves showing the changes in injection pressure of the hydrogel in Comparative Example 1 are shown. (a) shows the test results using mineralized water as the core testing fluid; (b) shows the test results using CH4 as the core testing fluid. Detailed Implementation The present invention will be further described below with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and technical features described in this application can be combined with each other. It should also be pointed out that, unless otherwise indicated, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. The terms "comprising" or "including" and similar words used in this invention refer to elements or objects preceding the word that encompass the elements or objects listed following the word and their equivalents, without excluding other elements or objects.

[0017] On one hand, the present invention provides a method for preparing carbon quantum dot-reinforced hydrogels, comprising the following steps: S1: Carbon quantum dots with amino, carboxyl, phenolic hydroxyl groups and aromatic rings on their surface are prepared using a carbon source, a nitrogen source and a modifier; the modifier is a mixture of hydroquinone and L-alanine.

[0018] In this invention, a mixture of hydroquinone and L-alanine is used as a modifier. Hydroquinone can provide phenolic hydroxyl active sites for carbon quantum dots, ensuring subsequent hydroxymethylation crosslinking reaction with hexamethylenetetramine (HMTA). L-alanine can introduce amino functional groups, improving the water dispersibility, temperature and salt resistance of carbon quantum dots. The two work synergistically to achieve functional modification of carbon quantum dots.

[0019] In one specific embodiment, the carbon source is any one or more of sodium citrate, citric acid, and glucose, and the nitrogen source is any one or more of urea, ethylenediamine, and o-phenylenediamine.

[0020] It should be noted that the carbon and nitrogen sources in the above embodiments are only preferred carbon and nitrogen sources of the present invention, and other carbon and nitrogen sources in the prior art that can prepare carbon quantum dots can also be applied to the present invention.

[0021] In one specific embodiment, the molar ratio of the carbon source, nitrogen source, hydroquinone, and L-alanine is 5~8:3:2~5:1.

[0022] In one specific embodiment, the carbon quantum dots are prepared by solid-state pyrolysis at a temperature of 170-210°C and a time of 0.8-1.2 h.

[0023] It should be noted that the solid-phase pyrolysis method in the above embodiments is only a preferred method for preparing carbon quantum dots in this invention. Other methods in the prior art that can prepare carbon quantum dots with amino, carboxyl, phenolic hydroxyl, and aromatic rings on the surface can also be applied to this invention.

[0024] S2: The carbon quantum dots are hydroxymethylated using hexamethylenetetramine to obtain hydroxymethylated carbon quantum dots.

[0025] In this invention, hexamethylenetetramine is used, which can slowly release formaldehyde to achieve mild and controllable hydroxymethylation. Furthermore, the nitrogen-containing heterocyclic structure of hexamethylenetetramine allows it to interact with the aromatic backbone of carbon quantum dots through π-π stacking and hydrogen bonding, subsequently enhancing the gel's thermal stability and salt resistance. Therefore, the hexamethylenetetramine of this invention cannot be replaced by other hydroxymethylating agents such as formaldehyde or paraformaldehyde.

[0026] In one specific embodiment, hydroxymethylation was performed at 60-80°C and pH 7.0-8.0 for 2-3 hours.

[0027] S3: Using the hydroxymethylated carbon quantum dots as a crosslinking agent, mix them with a polymer agent, a stabilizer, and a solvent to obtain the carbon quantum dot-reinforced hydrogel through a crosslinking reaction; the polymer agent can crosslink with the hydroxymethylated carbon quantum dots to form a dense and stable three-dimensional network.

[0028] In this invention, the hydroxymethylated carbon quantum dots are used as crosslinking agents. Their graphite-like carbon core structure can impart intrinsic thermal stability to the gel skeleton. At the same time, the abundant amino, carboxyl, and aromatic ring functional groups on their surface can construct a multivalent covalent crosslinking and π-π stacking network. The dense and stable three-dimensional network formed by crosslinking with the polymer main agent can keep the molecular chains of the hydrogel stretched in high temperature and high mineralization environment, enhance the resistance to thermal degradation, and prevent the hydrogel network from gradually loosening, dehydrating and shrinking, and the sealing strength from decreasing significantly.

[0029] In one specific embodiment, the mixture includes 0.4-0.8 wt% of a crosslinking agent, 0.6-1.0 wt% of a polymer base agent, 0.03-0.07 wt% of a stabilizer, and the balance being the solvent.

[0030] In one specific embodiment, the crosslinking reaction is carried out at 90~150°C for 6~12 hours.

[0031] In one specific embodiment, the polymer main agent is a temperature- and salt-resistant polyacrylamide, the stabilizer is any one or more of thiourea, sodium sulfite, sodium dithionite, and sodium isoascorbate, and the solvent is water. Optionally, the solvent is formation water.

[0032] It should be noted that the polymer main agent in the above embodiments is only a preferred polymer main agent of the present invention. Other heat- and salt-resistant polymers in the prior art that can crosslink with the hydroxymethylated carbon quantum dots to form a dense and stable three-dimensional network are also applicable to the present invention. The stabilizer is only a preferred stabilizer of the present invention. Other stabilizers in the prior art suitable for preparing hydrogels are also applicable to the present invention.

[0033] In one specific embodiment, the temperature- and salt-resistant polyacrylamide is any one or more of the following: acrylamide-acrylic acid-2-acrylamido-2-methylpropanesulfonic acid terpolymer sulfonated polyacrylamide (SAV55), AMPS modified copolymer polyacrylamide (SAV30), temperature- and salt-resistant sulfonated polyacrylamide (S-801), and acrylamide / AMPS / cationic monomer terpolymer (CPS-20).

[0034] In the above embodiments, taking SAV55 as an example, its molecular chain has sterically hindered sulfonic acid side groups, which can keep the molecular chain stretched in high temperature and high mineralization environment, and has strong resistance to thermal degradation. It can form a dense and stable three-dimensional network with carbon quantum dot composite crosslinking agent.

[0035] On the other hand, the present invention also provides a carbon quantum dot reinforced hydrogel prepared by any one of the above-described methods and its application in gas reservoir water control.

[0036] Example 1 A carbon quantum dot-reinforced hydrogel is prepared by the following steps: (1) Preparation of carbon quantum dots with amino, carboxyl, phenolic hydroxyl groups and aromatic rings on the surface Sodium citrate, urea, hydroquinone, and L-alanine were mixed in a molar ratio of 5:3:5:1 and ground into powder. 5 mL of deionized water was added and the mixture was ground for 20 min to form a homogeneous paste. The paste was transferred to an open crucible and placed in a muffle furnace for reaction at 190 °C for 1 h. The product was ground and ultrasonically washed with anhydrous ethanol until clear. After drying, it was dissolved in deionized water and filtered three times through a 0.22 μm filter membrane. The filtrate was transferred to a 100 KD ultrafiltration tube and centrifuged at 4000 r / min for 20 min. The supernatant from the outer tube was placed in a 1000 Da dialysis bag and dialyzed in deionized water for 48 h (changing the water every 6 h). The carbon quantum dots were then obtained by drying.

[0037] (2) Preparation of hydroxymethylated carbon quantum dots Add 50 mL of deionized water to a 250 mL three-necked flask, place the flask in a constant temperature water bath and heat to 70 °C, while adjusting the stirring speed of the stirring device to 300 rpm to maintain constant temperature and speed stirring. Slowly add 50 mL of HMTA reagent to the three-necked flask and stir continuously for 20 min until the solid reagent is completely dissolved to form a homogeneous and transparent HMTA aqueous solution; slowly add 25 mL of an aqueous dispersion containing 0.5 g of the product from step (1) (the carbon quantum dots account for 2% of the total mass of hydroxymethylated carbon quantum dots), maintaining a uniform stirring speed during the addition process, and continue stirring at a constant temperature for 30 min after the addition is completed to ensure that the carbon quantum dots are uniformly dispersed in the HMTA aqueous solution; slowly adjust the pH of the reaction system in the three-necked flask to 7.5 with 0.1 mol / L sodium hydroxide solution, maintain a constant temperature of 70 °C and a constant stirring speed of 300 rpm, and carry out a constant temperature reaction for 2.5 h to obtain liquid hydroxymethylated carbon quantum dots.

[0038] (3) Preparation of carbon quantum dot reinforced hydrogel Take 939.5 mL of formation water (mineralization 22 × 10⁻⁶). 4 Add 0.8 wt% of polymer SAV55 to a beaker, turn on the stirrer and adjust it to 400 r / min, and slowly add 4 h of polymer SAV55. Stir for 4 h until the polymer is completely dissolved. After dissolution, add 0.05 wt% of thiourea and stir for another 30 min. Then add 0.6 wt% of the product from step (2) and continue stirring for 15 min to ensure thorough mixing. Place the gelation solution in a 120℃ constant temperature oven and age for 8 h to form a carbon quantum dot reinforced hydrogel.

[0039] Example 2 Unlike Example 1, in step (1) of this example, the molar ratio of sodium citrate, urea, hydroquinone and L-alanine is 8:3:2:1.

[0040] Example 3 Unlike Example 1, in step (1) of this example, the molar ratio of sodium citrate, urea, hydroquinone and L-alanine is 7:3:7:1.

[0041] Example 4 Unlike Example 1, in step (1) of this example, the molar ratio of sodium citrate, urea, hydroquinone and L-alanine is 6:3:4:1.

[0042] Comparative Example 1 Unlike Example 1, this comparative example does not include step (1), and the substance added in step (2) is hydroquinone instead of carbon quantum dots.

[0043] Comparative Example 2 Unlike Example 1, hydroquinone was not added in step (1) of this comparative example, and the molar ratio of sodium citrate, urea and L-alanine was 5:3:1.

[0044] Comparative Example 3 Unlike Example 1, in step (1) of this comparative example, sodium citrate, urea, phenol and glycine were added in a molar ratio of 5:3:5:1.

[0045] Comparative Example 4 Unlike Example 1, in step (3) of this comparative example, instead of polymer SAV55, ordinary partially hydrolyzed polyacrylamide (HPAM) was added.

[0046] Test Example 1 The microstructure and particle size of the carbon quantum dots synthesized in Example 1 were characterized by electron microscopy, and the results are as follows: Figure 1 and Figure 2 As shown. From Figure 1 As can be seen, the carbon quantum dots synthesized in Example 1 exhibit a uniform distribution within the observation field, with no obvious aggregation, demonstrating excellent dispersibility. This characteristic is attributed to the electrostatic repulsion and steric hindrance effects generated by the surface functional groups after L-alanine modification. Morphologically, the vast majority of carbon quantum dots exhibit a regular spherical structure. Comparative analysis of images at different scales (50nm, 20nm, and 10nm) shows that... Figure 2As shown, the particle size was found to be concentrated in the range of 0.3–3.3 nm, consistent with the nanoscale characteristics of carbon quantum dots. Clear lattice fringes were observed in the high-resolution TEM image, further confirming the good crystallinity of the carbon quantum dots of this invention. The representative lattice spacing highly matches the characteristic lattice parameters of graphite-like carbon structures, indicating that the product has formed a stable graphite-like carbon core structure, fully demonstrating the successful synthesis of the target product, carbon quantum dots.

[0047] Test Example 2 The carbon quantum dots synthesized in Example 1 were characterized by atomic force microscopy, and the results are as follows: Figure 3 and Figure 4 As shown. From Figure 3 and Figure 4 It can be seen that the carbon quantum dots exhibit a uniform dot-like distribution, with excellent particle dispersion and no obvious agglomeration. Further analysis using height profile curves shows that their thickness is entirely within the nanoscale range. Figure 4 In (a), the particle height is approximately 10-65 nm. Figure 4 In (b), the particle height is approximately 10-35 nm. This thickness range is larger than the core particle size measured by TEM (1.2-1.5 nm), mainly due to the AFM tip broadening effect and the presence of an alanine modification layer on the particle surface. The results of both confirm that the carbon quantum dots in Example 1 are discrete nanoscale carbon quantum dot particles, and the synthesis was successful.

[0048] Test Example 3 The carbon quantum dots synthesized in Example 1 were characterized by Fourier transform infrared spectroscopy, and the results are as follows: Figure 5 As shown. From Figure 5 It can be seen that 3376cm - The absorption peak ¹ corresponds to the stretching vibrations of OH and NH, at 1603 cm⁻¹. - The absorption peak ¹ may be related to the stretching vibration of C=O, 1512 cm⁻¹ - The absorption peak ¹ may be related to the bending vibration of NH (amide II band), 1396 cm⁻¹ - The absorption peak ¹ may be related to the stretching vibration of CO (carboxylate), 1213 cm⁻¹ - The absorption peak at ¹ may be related to the stretching vibrations of COC or COH, while the peak at 834 cm⁻¹ is... - ¹ and 758cm - The absorption peak at ¹ is related to the out-of-plane bending vibration of the aromatic ring CH. The carbon quantum dots prepared in Example 1 of this invention contain amino, carboxyl, phenolic hydroxyl groups and aromatic rings on their surface.

[0049] Test Example 4 Thermogravimetric characterization was performed on the carbon quantum dots synthesized in Example 1, and the results are as follows: Figure 6 As shown. From Figure 6 It can be seen that the TG curve in the low temperature stage (30~118.21℃) shows that the sample mass is basically maintained at 100%, and the DTG curve only shows a slight fluctuation at 86.73℃. This stage corresponds to the slight removal of physically adsorbed water, which does not cause changes in the chemical structure of the material, indicating that the carbon quantum dots in Example 1 are structurally stable in the low temperature environment.

[0050] During the intermediate temperature range (118.21~193.45℃), the TG curve showed a rapid weight loss trend, while the DTG curve exhibited a significant weight loss peak at 193.45℃ (the weight loss rate reached its extreme). The mass loss in this stage mainly stemmed from two parts: firstly, the complete removal of surface-adsorbed water; and secondly, the thermal decomposition of the alanine-modified functional groups (amino, carboxyl, and alkyl groups) on the carbon quantum dots surface. This characteristic directly confirms the surface modification effect of L-alanine on carbon quantum dots.

[0051] During the medium-high temperature stage (193.45~522.82℃), the weight loss rate of the TG curve slowed down significantly, and the DTG curve showed no strong weight loss peak. During this stage, the small molecular functional groups (such as hydroxyl groups and CO bonds) at the defect sites on the carbon core surface undergo slow cleavage, further demonstrating the surface structural characteristics of carbon quantum dots.

[0052] During the high-temperature stage (522.82~799.22℃), the TG curve shows a continuous and slow weight loss, with the residual mass reaching 31.34% at 799.22℃. This stage represents the gradual carbonization process of the graphite-like carbon core in the carbon quantum dots. Due to the excellent high-temperature resistance of the graphite-like structure, the rate of residual mass loss gradually decreases with increasing temperature, indicating that its carbon core structure possesses good thermal stability.

[0053] Test Example 5 The gelation process of the gelation solutions in each embodiment and comparative example was observed every 1 hour. The gelation time of the system was obtained when the gel strength no longer changed. The sealing performance of each hydrogel system was tested. Specifically, artificial sandstone cores were filled into the holder and confining pressure was applied by a hand pump, maintaining the confining pressure 3 MPa higher than the axial pressure. The constant temperature oven was set to 120°C for 60 minutes to allow the displacement system and the core to fully reach the simulated formation temperature. In the evaluation of plugging performance, an ISCO dual-cylinder metering pump was first used to inject simulated formation water with optimal salinity into the core at a constant flow rate. The injection pressure and volume were recorded in real time. After the pressure stabilized, the initial aqueous permeability of the core was calculated using Darcy's formula. Subsequently, a 1PV hydrogel system was injected in reverse, with pressure and volume data recorded simultaneously. Valves at both ends of the core were closed, and the core was aged in a 120℃ oven for 12 hours to form a gel. After aging, the valves were opened, and simulated formation water was injected forward at a constant flow rate of 0.5mL / min. After the pressure stabilized, the aqueous permeability after plugging was calculated. The residual resistance coefficient and plugging rate were then calculated using the corresponding formulas to compare and evaluate the plugging performance of the system. The test results of some embodiments and some comparative examples are shown below. Figure 7 As shown in Table 1: Table 1. Hydrogel performance test results for each embodiment and comparative example.

[0054] In Table 1, the gel strength was obtained by macroscopic morphological characterization of the polymer gel samples after 30 days of aging using the Sydansk strength code method.

[0055] from Figure 7 As shown in Table 1, the traditional hydroquinone-hexamethylenetetramine system (No. 1) exhibits an F-level strength. The sample shows obvious stratification and water separation, with a large amount of yellow clear liquid precipitated at the bottom. The dehydration rate reaches 21% after 30 days of aging, indicating that its network structure has been partially destroyed during long-term aging and its stability is generally poor.

[0056] The carbon quantum dots modified with hydroquinone and L-alanine in this invention exhibit a superior performance gradient. Specifically: No. 2 has a G-level strength, with improved gel morphology compared to No. 1, achieving a G-level gel strength and a shorter gelation time; Nos. 3 and 4 have improved gel strength to H-level, with a more complete gel structure, only a small amount of water separation and shrinkage at the bottom, and dehydration rates reduced to 15% and 16% respectively, significantly enhancing stability; No. 5 shows the best performance, reaching I-level. This sample gel is dense and uniform overall, with no obvious layering or breakage, only a very small amount of sediment at the bottom of the bottle, and a dehydration rate of only 9% after 30 days of aging, while the shortest gelation time is 8 hours, achieving synergistic optimization of "rapid gelation" and "long-term stability".

[0057] As can be seen from the comparison, with the optimization of the carbon quantum dot graft structure, the gel strength gradually increased from grade F to grade I, and the dehydration rate decreased from 25% to 9%. This indicates that the carbon quantum dot-hexamethylenetetramine crosslinking agent can effectively construct a denser and more aging-resistant polymer network. It is the candidate system with the best overall performance among all formulations, and provides a more promising new crosslinking agent solution for gas field profile control and water shut-off.

[0058] Comparative Example 2: The carbon quantum dots without added hydroquinone dot surface lack phenolic hydroxyl functional groups, making it unable to undergo effective hydroxymethylation with hexamethylenetetramine. This hinders the crosslinking process, resulting in a gel strength of only D grade, failing to form a stable and complete gel structure. At 120℃ and a mineralization of 22 × 10⁻⁶, the crosslinking was also unsuccessful. 4 After aging for 30 days under mg / L conditions, the system dehydration rate exceeded 45%, exhibiting severe water separation and collapse. The core plugging rate was below 40%, failing to demonstrate long-term plugging performance and selective gas-water plugging effectiveness. This proves that hydroquinone is an indispensable modifying component for achieving efficient cross-linking of carbon quantum dots and constructing a stable gel network in this invention. The phenolic hydroxyl groups it provides are the core active sites for hydroxymethylation reactions and the formation of high-strength cross-linked structures. The lack of hydroquinone directly leads to the overall failure of the gel system.

[0059] Comparative Example 3: After replacing the modifier, carbon quantum dots at 22 × 10⁻⁶ 4 After aging in high-mineralized water at mg / L for 30 days, significant agglomeration and precipitation occurred, indicating insufficient dispersibility. The gel strength of the system only reached grade F, failing to form a high-strength gel. The dehydration rate after 30 days of aging was as high as 28%, the core plugging rate was only 72.43%, and the gas-water selectivity was poor. The standardized fluid resistance ratio N was also low. frr =2.1, which is far lower than the system of this invention and cannot meet the requirements for long-term water control in high-temperature and high-salinity gas reservoirs. This proves that the combination of hydroquinone and L-alanine is the optimal modifier combination for the system of this invention. The synergy between the two can simultaneously achieve high reactivity, high salt dispersibility and thermal stability of carbon quantum dots, which cannot be achieved by other modifier combinations.

[0060] Comparative Example 4 selected ordinary HPAM as the polymer main agent, which was tested at 120℃ and 22×10⁻⁶ ℃. 4 Under high salinity conditions (mg / L), molecular chain degradation, coiling, and precipitation easily occur, making it unable to form a stable three-dimensional network structure with carbon quantum dot crosslinking agents. The system's gel strength is only grade E, the dehydration rate after 30 days of aging is as high as 38%, the core plugging rate is less than 65%, gas-water selectivity is poor, and the standardized fluid resistance ratio (N) is low. frr =1.3, lacking the selective sealing capability of "blocking water but not gas", and unable to meet the engineering requirements for long-term water control in high-temperature and high-salinity gas reservoirs.

[0061] Test Example 6 The injection performance of the hydrogels in each example and comparative example was tested. Specifically, the hydrogel system was injected in reverse at a constant flow rate of 0.3 mL / min into the core, and the injection pressure changes were recorded in real time. The test results for Example 1 and Comparative Example 1 are as follows: Figure 8 As shown.

[0062] Depend on Figure 8 As shown in (a), during the injection process of the carbon quantum dot-reinforced hydrogel of this invention, the pressure was maintained at a relatively low level of 0.024–0.028 MPa in the early water injection stage. After entering the system injection stage, the pressure rapidly increased and reached a peak value of 0.081 MPa near 2.0–2.2 PV. Subsequently, although the pressure dropped somewhat during the subsequent water injection process, it eventually stabilized at 0.065 MPa, which was significantly higher than the initial water injection pressure. This indicates that the system formed a strong and stable residual resistance in the core pore medium, demonstrating good injection control ability and continuous sealing performance.

[0063] contrast Figure 8 As shown in (b), the pressure of the traditional crosslinking agent hydrogel remained within the range of 0.024–0.028 MPa during the initial water injection stage. After injection, the pressure increased rapidly and reached a peak near 2.0–2.2 PV, with a maximum of 0.078 MPa. As subsequent water injection continued, the pressure gradually decreased and eventually stabilized within the range of 0.056–0.057 MPa.

[0064] In comparison, the carbon quantum dot-reinforced hydrogel of this invention exhibits higher peak pressure and a higher subsequent stable pressure plateau, indicating that it has stronger drag-increasing ability, better plugging stability, and superior continuous control effect in rock cores.

[0065] Test Example 7 The plugging performance of the hydrogels in each example and comparative example was tested. A 1PV hydrogel system was injected in reverse at a constant flow rate of 0.3 mL / min. After injection, the core was placed in a 120℃ constant temperature oven for 12 hours (simulating gas reservoir formation temperature) to allow the hydrogel system to fully cross-link into a gel. Subsequently, simulated formation water was injected in the forward direction at a flow rate of 0.5 mL / min to evaluate the plugging effect of each hydrogel. The initial fluid permeability of the core before plugging was recorded as K1, and the fluid permeability measured after subsequent water injection to reach a stable state was recorded as K2. The plugging rate and residual resistance coefficient were calculated based on these values. The results for Example 1 and Comparative Example 1 are shown in Table 2. Table 2 Comparison of sealing performance between Example 1 and Comparative Example 1

[0066] As shown in Table 2, after sealing, the permeability of the core fluid in the carbon quantum dot-reinforced group of Example 1 decreased from 98.7 mD to 7.29 mD, with a sealing rate of 92.61% and a residual resistance coefficient of 13.54. In contrast, the permeability of the core fluid in the traditional crosslinking agent group of Comparative Example 1 decreased from 95.2 mD to 15.6 mD, with a sealing rate of 83.61% and a residual resistance coefficient of 6.10. The experimental results show that both systems can form a certain sealing effect in the core, but the enhanced system of Example 1 is more effective in reducing the seepage capacity of the core and increasing the residual resistance. Combined with the injection pressure change pattern, it can be seen that the enhanced group of Example 1 can still maintain a stable pressure plateau of about 0.065 MPa in the subsequent water injection stage, while the stable pressure of the traditional crosslinking agent group is about 0.056-0.057 MPa, indicating that the enhanced system of Example 1 formed a stronger and more stable sealing structure in the core.

[0067] To evaluate the long-term plugging stability of the two hydrogel systems under high-temperature conditions, a constant-temperature aging experiment was conducted on the core samples at 120℃. The liquid permeability of the aged core samples was measured at 1, 5, 10, 20, and 30 days. The plugging rate and residual resistance coefficient were further calculated. The results are shown in Tables 3 and 4. Table 3. Blocking efficiency and residual drag coefficient of the enhanced hydrogel system in Example 1

[0068] Table 4. Blocking efficiency and residual drag coefficient of the conventional crosslinking agent hydrogel system in Comparative Example 1

[0069] As shown in Tables 3 and 4, the reinforced hydrogel system of Example 1 exhibits excellent long-term stability. With prolonged aging time, the overall plugging performance of the reinforced group showed little change: after 10 days of aging, the plugging rate reached a maximum of 93.40%, and the residual resistance coefficient increased to 15.14, indicating that the gel continued to cross-link in the core pores, and the network structure became further denser; after 30 days of aging, the plugging rate remained at 92.53%, and the residual resistance coefficient was 13.38, only slightly lower than the initial value (1 day), indicating that the system still possesses good structural stability and continuous plugging ability under high-temperature conditions.

[0070] This superior performance is mainly attributed to the synergistic enhancement effect of Example 1. On the one hand, its graphite-like carbon core structure has high thermal stability, which helps to improve the thermal degradation resistance of the gel system; on the other hand, its abundant oxygen- and nitrogen-containing functional groups on the surface can form multiple interactions with the polymer and crosslinking system, further enhancing the stability of the gel network structure.

[0071] Test Example 8 The gas-water selective plugging performance of the hydrogels in each embodiment and comparative example was tested. The basic core parameters used in Example 1 and Comparative Example 1 are shown in Table 5, and the injection pressure variation curves are shown in Table 5. Figure 9 and Figure 10 As shown in Table 6, the changes in core parameters before and after injection are as follows: Table 5 Basic parameters of the core

[0072] Table 6 Basic parameters of the core

[0073] Depend on Figure 9 and Figure 10 It can be seen that the pressure difference evolution characteristics of the two hydrogel systems in Example 1 and Comparative Example 1 under liquid / gas phase conditions are significantly different. In the liquid phase, the pressure difference of the hydrogel-reinforced system in Example 1 establishes rapidly and stabilizes at a low level during the initial water injection. After injection, the pressure difference rises sharply, reaching a peak at approximately 3.2–3.4 PV. Although it slightly decreases during subsequent water injection, it remains at a relatively high level overall, indicating that the system has a strong blocking effect on the aqueous phase. In the gas phase, the initial pressure build-up is slower, and the stable pressure difference is significantly lower than that in the liquid phase. After injection, the pressure difference also increases and reaches a peak in the initial stage of subsequent gas injection, but the peak value and the later stable plateau are both lower than those in the liquid phase, indicating that the system has a relatively weak blocking effect on gas phase seepage. The pressure difference increase of the hydrogel system in the liquid phase is relatively limited, and both the peak value and the stable pressure are lower than those of the reinforced system in Example 1. In the gas phase, the pressure difference response is still more significant, and the difference between the liquid and gas phases is not as significant as that of the reinforced system in Example 1, indicating that it also has a strong blocking effect on the gas phase, but its selective blocking ability is relatively weak. In summary, the enhanced hydrogel system in Example 1, while ensuring high water-blocking capability, has less impact on gas phase permeation, exhibiting superior "water-blocking without gas-blocking" performance.

[0074] Table 6 shows the experimental results of core parameter changes before and after injection for the two systems. It is evident that the enhanced hydrogel system in Example 1 significantly improved the sealing performance of the aqueous phase compared to the gas phase. The permeability of the liquid phase Y-5 core decreased from 11.26 mD to 1.05 mD, achieving a sealing rate of 90.68% and a residual resistance coefficient of 10.72. In the gas phase Y-6 core, the permeability decreased from 26.20 mD to 9.58 mD, achieving a sealing rate of 63.44% and a residual resistance coefficient of 2.74. Based on these results, the standardized fluid resistance ratio N was calculated. frr=3.91 (much greater than 1), indicating that the system has outstanding selective blocking ability between gas and water, effectively blocking water while reducing the impact on gas phase seepage. In contrast, the selective blocking ability of the traditional crosslinking agent hydrogel system in Comparative Example 1 is weaker. The permeability of the liquid phase Y-7 core decreased from 12.04 mD to 4.82 mD, with a blocking rate of 59.97% and a residual resistance coefficient of 2.50; the permeability of the gas phase Y-8 core decreased from 25.40 mD to 11.23 mD, with a blocking rate of 55.79% and a residual resistance coefficient of 2.26, yielding N frr =1.11 (slightly greater than 1). This indicates that the traditional system has a similar degree of blocking effect on the aqueous and gas phases, with little difference between water and gas, exhibiting the characteristic of "blocking water and blocking gas simultaneously". The reason for this difference is that the enhanced hydrogel system in Example 1 significantly improves the water blocking ability while causing significantly less damage to the gas phase permeability, exhibiting superior water control and gas repellency performance.

[0075] It should be noted that the above test examples are only test results of some embodiments of the present invention. Other embodiments have similar effects to Example 1, all of which can maintain a dense and complete three-dimensional structure under high temperature and high mineralization conditions, overcoming the defects of conventional gels that are prone to thermal degradation and dehydration shrinkage under harsh conditions. Furthermore, they possess excellent selective blocking characteristics of "blocking water but not gas," effectively controlling water intrusion while maximizing the protection of gas-phase energy production. In addition, the above embodiments are only some embodiments of the present invention. Carbon quantum dot-reinforced hydrogels with the above properties prepared by changing the types and amounts of carbon and nitrogen sources, as well as parameters such as temperature and time, also fall within the scope of the present invention.

[0076] The above description is merely a representative embodiment of the present invention and is not intended to limit the present invention in any way. Any embodiment made by those skilled in the art without departing from the scope of the present invention and utilizing the disclosed technical content is an equivalent embodiment of the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a carbon quantum dot-reinforced hydrogel, characterized in that, Includes the following steps: S1: Carbon quantum dots with amino, carboxyl, phenolic hydroxyl groups and aromatic rings on their surface are prepared using a carbon source, a nitrogen source and a modifier; the modifier is a mixture of hydroquinone and L-alanine; S2: The carbon quantum dots are hydroxymethylated with hexamethylenetetramine to obtain hydroxymethylated carbon quantum dots; S3: Using the hydroxymethylated carbon quantum dots as a crosslinking agent, mix them with a polymer agent, a stabilizer, and a solvent to obtain the carbon quantum dot-reinforced hydrogel through a crosslinking reaction; the polymer agent can crosslink with the hydroxymethylated carbon quantum dots to form a dense and stable three-dimensional network.

2. The method for preparing carbon quantum dot-reinforced hydrogel according to claim 1, characterized in that, In step S1, the carbon source is any one or more of sodium citrate, citric acid, and glucose, and the nitrogen source is any one or more of urea, ethylenediamine, and o-phenylenediamine.

3. The method for preparing carbon quantum dot-reinforced hydrogel according to claim 1, characterized in that, In step S1, the molar ratio of the carbon source, nitrogen source, hydroquinone, and L-alanine is 5~8:3:2~5:

1.

4. The method for preparing carbon quantum dot-reinforced hydrogel according to claim 1, characterized in that, In step S1, the carbon quantum dots are prepared by solid-state pyrolysis at a temperature of 170-210°C and a time of 0.8-1.2 h.

5. The method for preparing carbon quantum dot-reinforced hydrogel according to claim 1, characterized in that, In step S2, hydroxymethylation is carried out at 60-80°C and pH 7.0-8.0 for 2-3 hours.

6. The method for preparing carbon quantum dot-reinforced hydrogel according to claim 1, characterized in that, In step S3, the mixing process includes 0.4-0.8 wt% of crosslinking agent, 0.6-1.0 wt% of polymer main agent, 0.03-0.07 wt% of stabilizer, and the balance being the solvent.

7. The method for preparing carbon quantum dot-reinforced hydrogel according to claim 1, characterized in that, In step S3, the crosslinking reaction is carried out at 90~150℃ for 6~12h.

8. The method for preparing carbon quantum dot-reinforced hydrogels according to any one of claims 1-7, characterized in that, In step S3, the polymer main agent is a temperature- and salt-resistant polyacrylamide, the stabilizer is any one or more of thiourea, sodium sulfite, sodium dithionite, and sodium isoascorbate, and the solvent is water.

9. A carbon quantum dot-reinforced hydrogel, characterized in that, It was prepared using the method for preparing carbon quantum dot reinforced hydrogel according to any one of claims 1-8.

10. The application of the carbon quantum dot reinforced hydrogel as described in claim 9 in water control in gas reservoirs.